Antibacterial activity of peptaibols from Trichoderma longibrachiatum SMF2 against gram-negative Xanthomonas oryzae pv. oryzae, the causal agent of bacterial leaf blight on rice - Zhang, Yu-Qiang; Zhang, Shan; Sun, Mei-Ling; Su, Hai-Nan; Li, Hao-Yang; Kun-Liu,; Zhang, Yu-Zhong; Chen, Xiu-Lan; Cao, Hai-Yan; Song, Xiao-Yan (Frontiers in Microbiology, 2022)
Bacterial leaf blight caused by Gram-negative pathogen Xanthomonas oryzae pv. oryzae (Xoo) is one of the most destructive bacterial diseases on rice. Due to the resistance, toxicity and environmental issues of chemical bactericides, new biological strategies are still in need. Although peptaibols produced by Trichoderma spp. can inhibit the growth of several Gram-positive bacteria and plant fungal pathogens, it still remains unclear whether peptaibols have anti-Xoo activity to control bacterial leaf blight on rice. In this study, we evaluated the antibacterial effects of Trichokonins A (TKA), peptaibols produced by Trichoderma longibrachiatum SMF2, against Xoo. The in vitro antibacterial activity analysis showed that the growth of Xoo was significantly inhibited by TKA, with a minimum inhibitory concentration of 54 μg/mL and that the three TKs in TKA all had remarkable anti-Xoo activity. The inhibitory mechanism analysis showed that TKA treatment resulted in the damage of Xoo cell morphology and the release of intracellular substances, such as proteins and nucleic acids, from Xoo cells, suggesting the damage of the permeability of Xoo cell membrane by TKA. The pathogenicity analysis showed that the lesion length on rice leaf was significantly reduced by 82.2% when treated with 27 μg/mL TKA. This study represents the first report on the antibacterial activity of peptaibols against a Gram-negative bacterium. The results suggest that TKA may have a promising potential in controlling bacterial leaf blight on rice.